CLASSIFICATION OF COMMUNICATION TECHNOLOGIES SOCIAL ENGINEERING IN THE NEWSPAPERS OF THE REICHSCOMISARIAT "UKRAINE" (FROM SEPTEMBER, 1, 1941 FOR JULY, 17, 1942) - Kholod, А. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
In the article an author formulates an aim: to describe and classify of communication technologies of the social engineering in the newspapers of Reichscommissariat "Ukraine" (RCU) in a period from September, 1, 1941 to July, 17, 1942. On results research: 1) it is set that more active than all in the newspapers of (RCU) on the first year his existence technologies of the first stage of the social engineering (namely are authentications) were used; 2) actively enough the authors of journalistic materials called to of communication technologies that declared "diffuse" character of confluence of two stages of the social engineering, namely are authentications and designs; 3) the no active enough (only in 9%) journalists of fascist newspapers of (RCU) called to of communication technologies of the stage of design of reality. Conclusions: the authors of journalistic materials did not aim to design future reality of "new order" of "Greatgermanium", and also did not have sufficient journalistic preparation and experience for realization Goebels and Hitler intentions.